The role of miRNAs in T helper cell development, activation, fate decisions and tumor immunity - Xu, Shi-Jun; Chen, Jin-Hua; Chang, Suhwan; Li, Hai-Liang (Frontiers in Immunology, 2024)
T helper (Th) cells are central members of adaptive immunity and comprise the last line of defense against pathogen infection and malignant cell invasion by secreting specific cytokines. These cytokines then attract or induce the activation and differentiation of other immune cells, including antibodyproducing B cells and cytotoxic CD8 + T cells. Therefore, the bidirectional communication between Th cells and tumor cells and their positioning within the tumor microenvironment (TME), especially the tumor immune microenvironment (TIME), sculpt the tumor immune landscape, which affects disease initiation and progression. The type, number, and condition of Th cells in the TME and TIME strongly affect tumor immunity, which is precisely regulated by key effectors, such as granzymes, perforins, cytokines, and chemokines. Moreover, microRNAs (miRNAs) have emerged as important regulators of Th cells. In this review, we discuss the role of miRNAs in regulating Th cell mediated adaptive immunity, focusing on the development, activation, fate decisions, and tumor immunity.